2020
DOI: 10.3390/su12177211
|View full text |Cite
|
Sign up to set email alerts
|

The Implementation of Strategic Management in Greek Hospitality Businesses in Times of Crisis

Abstract: The aim of this research was to explore the implementation of strategic management approaches in Greek tourism and hospitality businesses during economic crises, in order to further expand our current knowledge of operating in a turbulent environment and embracing novel aspects by linking economic crises with the current literature on the COVID-19 pandemic. This research emphasizes the connection between the strategic management approaches of 131 tourism organizations and hospitality business performance by an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
24
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(27 citation statements)
references
References 65 publications
2
24
0
1
Order By: Relevance
“…Nevertheless, to the best of our knowledge, the previous literature has not found a crisis solution for tourism industry stakeholders. Most of the early literature may be limited to the exploration of a wide range of issues related to the quantitative or qualitative nature of second-hand data analysis related to tourism issues [23][24][25][26][27], tourism management issues and related strategic issues under the pandemic [28][29][30][31][32][33], and the satisfaction issues of accommodation and restaurants under the pandemic [34][35][36][37]. Some of the researchers study the economic issues that affect the tourism industry in the COVID-19 pandemic [38][39][40][41][42][43][44], discuss the psychological issues of travel stakeholders in the pandemic [45][46][47][48][49][50], or perform research on Tourism and Virtual Reality (VR) [51][52][53].…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, to the best of our knowledge, the previous literature has not found a crisis solution for tourism industry stakeholders. Most of the early literature may be limited to the exploration of a wide range of issues related to the quantitative or qualitative nature of second-hand data analysis related to tourism issues [23][24][25][26][27], tourism management issues and related strategic issues under the pandemic [28][29][30][31][32][33], and the satisfaction issues of accommodation and restaurants under the pandemic [34][35][36][37]. Some of the researchers study the economic issues that affect the tourism industry in the COVID-19 pandemic [38][39][40][41][42][43][44], discuss the psychological issues of travel stakeholders in the pandemic [45][46][47][48][49][50], or perform research on Tourism and Virtual Reality (VR) [51][52][53].…”
Section: Introductionmentioning
confidence: 99%
“…With the advancement of human society, the assessment of tourism competitiveness cannot be based only on primary consideration on tourism performance and competitive advantages, but from a more progressive insight. In particular, how to promote the sustainable tourism competitiveness through enhancing entrepreneurship ecosystem [27], constructing the positive relationships between the government and tourism development [43], and optimizing business management environment [3,4,25,26,44] has become a meaningful research issue, which leads to the suitable measures, and a conceptual framework utilized to evaluate a tourist destination competitiveness requires a critical investigation of the literature to identify the sufficient reinforcement of information on the destination business environment (DBE) and destination competitive advantages (DCA). That is, the determinants that affect the competition level of tourism destinations must be essentially related to the competitiveness of tourism-related constituent firms and based on the generic business strategy views identified by Porter [42], Miles and Snow [14], and Stevenson and Jarillo [15].…”
Section: Tourism Competitiveness and Its Applicationsmentioning
confidence: 99%
“…Compared with tourist perspective, it is more convincing to analyze destination competitiveness from a business perspective, which is supportive because the various stakeholders with rich tourism business experience are the real specialists in formulating accurate decisions and assessing objective investment conditions while complying with local regulations [45,48]. The most recent research demonstrated that the sustainable destination management inputs and competitiveness are inseparable from technology innovation, business management environment, entrepreneurship, and government supports [18,[25][26][27]43,44,49].…”
Section: Tourism Competitiveness From the Perspective Of The Businessmentioning
confidence: 99%
See 1 more Smart Citation
“…A study by Malinovsky et al [4] observes that Russian economy has been strongly negatively affected by the restrictions and worsened macroeconomic indicators are also expected in the future. In relation to individual industries Varelas and Apostolopoulos [5] for example analysed the strategic approaches to management among entities involved in tourism, which were focused on the mitigation of the economic impacts. Restrictions introduced to prevent the virus from spreading have changed the life style from the roots, which has also accented social inequality.…”
Section: Introductionmentioning
confidence: 99%